Exploring Work-Related Stress among Indonesian Primary School Teachers: A Study in the Post-Covid-19 Era - Agung, Anak Agung Gede; Gading, I Ketut; Agetania, Ni Luh Putu; Prawira, Anak Agung Gede Oka Ananta; Deng, Jian-Bang; Werang, Basilius Redan (Journal of Ecohumanism, 2024)
Teachers' well-being is closely linked to their ability to teach effectively. Stress can impact their teaching performance, which in turn affects student learning outcomes. This study aimed to explore the work-related stress of primary school teachers in Bali Province, Indonesia. To address this objective comprehensively, we utilized a mixed research approach, combining both quantitative and qualitative research approaches. Quantitative data were collected by distributing a questionnaire of 10 items, while qualitative data were obtained through interviews with some of the surveyed teachers. Obtained quantifiable data were subjected to descriptive statistical analysis techniques, while quantitative data were subjected to descriptive qualitative analysis techniques. The results from both the descriptive statistical and qualitative analyses revealed a significantly high level of work-related stress among primary school teachers in Bali Province, Indonesia. The high levels of reported stress underline the critical need for educational policymakers to create and implement solutions for lowering teacher stress. This could entail modifying administrative requirements, providing support resources, and generating more manageable workloads.